Surveillance Kejadian Phlebitis pada Pemasangan Kateter Intravena pada Pasien Rawat Inap di Rumah Sakit Ar. Bunda Prabumulih - Wahyu Rizky; Supriyatiningsih Supriyatiningsih (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Incidence of phlebitis is an indicator of the quality of hospital services with minimal rate of ≤1.5% standard. The incidence of phlebitis in Hospital AR. Bunda Prabumulih is still high ranging from 10% to 16%. Highest incidence of phlebitis is in April amounted to 16%. Surveillance is an important activity for the planning, implementation, evaluation and infection control practices. This was an observational study with a descriptive analytic approach, while for non-experimental research design was a prospective cohort quantitative approach. The aim was to know the incidence of intravenous catheter phlebitis, knowing the factors supporting the cause of intravenous catheter phlebitis, and to understand what kind of germs that cause the occurrence of phlebitis in patients hospitalized in AR. Bunda Prabumulih Hospital. Large samples obtained were 17 people who had phlebitis. From the results, the percentage of incidence of phlebitis in Hospital AR. Bunda Prabmulih in June 2013 amounted to 333.33‰. The incidence of phlebitis was happeningmostly in age of 31-50 years at 41.2%. The phlebitis occured in women at 64.7%. Types of microorganisms found in phlebitis patients, namely: staphylococcus, E.coli and staphylococcus aureus. Factors which may cause the occurrence of phlebitis were the type of ﬂ uid used, types of bacteria, especially species of gram-positive bacteria, and the principle of sterilization during intravenous procedures by health workers. Additionaly, The incidence of phlebitis in Hospital AR. Bunda Prabumulih in June 2013 amounted to 333.33‰ much larger than the standard set by the Depkes RI is ≤1.5%.